2013
DOI: 10.1007/s00426-013-0515-7
|View full text |Cite
|
Sign up to set email alerts
|

Auditory spatial negative priming: What is remembered of irrelevant sounds and their locations?

Abstract: The categorization and identification of previously ignored visual or auditory stimuli is typically slowed down--a phenomenon that has been called the negative priming effect and can be explained by the episodic retrieval of response-inadequate prime information and/or an inhibitory model. A similar after-effect has been found in visuospatial tasks: participants are slowed down in localizing a visual stimulus that appears at a previously ignored location. In the auditory modality, however, such an after-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
2
8
2
Order By: Relevance
“…Recently, Frings et al (2014) demonstrated that the size of tactile spatial NP is not modulated by whether or not there is a mismatch between the target and distractor features presented at the repeated location (i.e., the prime distractor and the probe target). This pattern of results is in line with what has previously been obtained in vision (see, e.g., Milliken et al, 1994;Tipper et al, 1995), whereas it contrasts with what has been seen in audition (where spatial NP was evident only when feature mismatch was present; Mayr et al, 2009;Mayr et al, 2014;Möller et al, 2013). Thus, Frings et al (2014) provided indicative evidence that touch behaves like vision when it comes to spatial NP, insofar as in touch and vision the perceptual interference during probe encoding seems not to be as important for spatial NP.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Recently, Frings et al (2014) demonstrated that the size of tactile spatial NP is not modulated by whether or not there is a mismatch between the target and distractor features presented at the repeated location (i.e., the prime distractor and the probe target). This pattern of results is in line with what has previously been obtained in vision (see, e.g., Milliken et al, 1994;Tipper et al, 1995), whereas it contrasts with what has been seen in audition (where spatial NP was evident only when feature mismatch was present; Mayr et al, 2009;Mayr et al, 2014;Möller et al, 2013). Thus, Frings et al (2014) provided indicative evidence that touch behaves like vision when it comes to spatial NP, insofar as in touch and vision the perceptual interference during probe encoding seems not to be as important for spatial NP.…”
Section: Discussionsupporting
confidence: 91%
“…In other words, auditory spatial NP is eliminated when there is no mismatch between the stimulus features encoded at the repeated location (prime distractor, probe target). That is, feature mismatch is crucial for auditory spatial NP (Mayr et al, 2009;Mayr et al, 2014;Möller et al, 2013), yet it does not impact strongly on visuospatial NP Tipper, Weaver, & Milliken, 1995). Taken together, visuospatial NP has been shown first to reflect the aftereffects of the inhibition of previously activated responses, and second, is independent of feature mismatch.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…It should be noted that for auditory location NP (Mayr, Hauke, & Buchner, 2009;Mayr, Buchner, Möller, & Hauke, 2011;Mayr, Möller, & Buchner, 2014) a pattern of results has been observed that diverges from the ones observed in vision (Milliken et al, 1994) or touch (Frings, Mast, & Spence, 2014). Spatial NP was found (i.e.…”
Section: Np In Different Modalitiesmentioning
confidence: 91%
“…The latter aspect is further pursued in the empirical contribution by Mayr, Möller, and Buchner (2014). Mayr and colleagues investigate the mechanisms underlying auditory spatial negative priming.…”
mentioning
confidence: 99%